The Influence of Family Environment, Financial Literacy, Future Perception, and Self-Control on Saving Behavior Mediated by An Intention of High School Students in Jepara (Universitas Negeri Semarang, 2022)
Saving behavior is the behavior of saving by setting aside a number of money owned. The aim of this study is to analyze the influence of family environment, financial literacy, future perception, and self-control on saving behavior that mediated by the intention of high school students in Jepara. The research was conducted using a survey. The population of the study was 1,315 of high school students in Jepara. By using random sampling technique, the researcher got 307 students as the sample of the study. The data collection method was done by using a questionnaire. The researcher used a path analysis to analyze the data. The results showed that the family environment influenced the saving behavior through intention with a total effect value for 5.39%, financial literacy influenced the saving behavior through intention with the total effect value for 3.73%. Future perception did not influence the saving behavior through intention with the total effect value for 2.93%, and self-control influenced the saving behavior through intention with a total effect value for 20.52%.